Groundwater remediation and treatment technologies - Cheremisinoff, Nicholas P. (Noyes Publications, 1997)
This volume has been organized for practicing engineers who deal with the problems of groundwater and leachate remediation. It is intended to provide a practical overview of both techniques for evaluating groundwater quality and in selecting remediation technologies that are cost effective. Emphasis is given to advanced remediation methods.